2016
DOI: 10.1111/jeb.12995
|View full text |Cite
|
Sign up to set email alerts
|

Brain size evolution in pipefishes and seahorses: the role of feeding ecology, life history and sexual selection

Abstract: Brain size varies greatly at all taxonomic levels. Feeding ecology, life history and sexual selection have been proposed as key components in generating contemporary diversity in brain size across vertebrates. Analyses of brain size evolution have, however, been limited to lineages where males predominantly compete for mating and females choose mates. Here, we present the first original data set of brain sizes in pipefishes and seahorses (Syngnathidae) a group in which intense female mating competition occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 85 publications
(150 reference statements)
1
10
0
Order By: Relevance
“…An interspecific analysis of trophic ecology in syngnathid fishes is consistent with this hypothesis, and indicates that long-snouted species consume significantly more mobile and smaller prey than do species with short snouts (Kendrick and Hyndes 2005). Increases in snout to head length ratios have also been associated with increases in brain size in this group, a relationship that may reflect the importance of enhanced visual information processing when feeding on highly mobile prey (Tsuboi et al 2017).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…An interspecific analysis of trophic ecology in syngnathid fishes is consistent with this hypothesis, and indicates that long-snouted species consume significantly more mobile and smaller prey than do species with short snouts (Kendrick and Hyndes 2005). Increases in snout to head length ratios have also been associated with increases in brain size in this group, a relationship that may reflect the importance of enhanced visual information processing when feeding on highly mobile prey (Tsuboi et al 2017).…”
supporting
confidence: 60%
“…Increases in snout to head length ratios have also been associated with increases in brain size in this group, a relationship that may reflect the importance of enhanced visual information processing when feeding on highly mobile prey (Tsuboi et al. ).…”
mentioning
confidence: 89%
“…The nervous system was completely formed in H. guttulatus newborns, with a progressive increase in size of the optic tectum and differentiation of pituitary gland and saccus vasculosus. A recent study on the evolution of the brain in Sygnathidae (Tsuboi et al ., ) supports the hypothesis that brain development is based on evolutionary capabilities adapted to feeding on highly mobile prey, so that the processing of visual information led to larger brain sizes compared with species that feed on less mobile prey (Tsuboi et al ., ). Environmental adaptation also contributes to modifications in the brain structure, resulting in increased eye size in planktivorous fish and an enlargement of the optic tectum in species feeding on fast‐moving prey (Kotrschal et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the field of evolutionary neuroscience have shown that the physiological and reproductive behaviors of a species are reflected in the structure of the CNS (Kotrschal et al 1998, Gonzalez-Voyer et al 2016, Tsuboi et al 2017. We show that the brain of H. barbouri contains a large optic tectum, whereas the size of the cerebellum is not abnormal.…”
Section: Discussionmentioning
confidence: 48%
“…Although no information is available on the feeding ecology of this species during the first month of development, our finding probably reflects the structurally complex habitat where H. barbouri catches prey. This may be a unique characteristic for syngnathid fish since they commonly have the longest snout and consume highly mobile prey, such as mysids, shrimps and fish (Kotrschal et al 1998, Kendrick and Hyndes 2005, Garamszegi et al 2005, de Lussanet and Muller 2007, Van Wassenbergh et al 2011, MacLean et al 2014, Lefebvre et al 2016, Tsuboi et al 2017.…”
Section: Discussionmentioning
confidence: 99%